2020
DOI: 10.3346/jkms.2020.35.e372
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak and Its Association with Healthcare Workers' Emotional Stress: a Cross-Sectional Study

Abstract: Background The coronavirus disease 2019 (COVID-19) outbreak has exposed healthcare workers to extreme physical workloads and psychological challenges. Thus, we aimed to assess the immediate correlates of emotional stress and to identify which specific jobs, departments, and exposure types are risk factors for emotional stress in healthcare workers. Methods In this cross-sectional study conducted from April 2 to 10, 2020, university hospital workers were administered sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…In nurses during the MERS outbreak, perceived social stigma was associated with higher stress and poorer mental health ( 108 ). Similarly, during the COVID-19 pandemic, HCW who felt stigmatized, perceived stigma concerning negative public attitudes and disclosing about one's work, experienced higher levels of depression, anxiety, and psychological distress ( 55 , 78 , 102 , 108 , 109 , 116 , 138 ). During the SARS outbreak, HCW who felt people avoided their family because of their job were twice as likely to have elevated levels of post-traumatic stress symptoms ( 83 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In nurses during the MERS outbreak, perceived social stigma was associated with higher stress and poorer mental health ( 108 ). Similarly, during the COVID-19 pandemic, HCW who felt stigmatized, perceived stigma concerning negative public attitudes and disclosing about one's work, experienced higher levels of depression, anxiety, and psychological distress ( 55 , 78 , 102 , 108 , 109 , 116 , 138 ). During the SARS outbreak, HCW who felt people avoided their family because of their job were twice as likely to have elevated levels of post-traumatic stress symptoms ( 83 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies conducted during COVID-19 found that risk of contact was not associated with greater distress (53,94,132). Spending time in quarantine due to risk of being infected was associated with higher levels of burnout, depression, and psychological distress in HCW during SARS and COVID-19 (14,59,92,132), but was unrelated to posttraumatic stress symptoms and psychological distress in HCW during the MERS outbreak or the COVID-19 outbreak (78,85,109,125,156). Lastly, one study found that HCW who had colleagues who became infected, had deceased due to infection, or had been quarantined, also experienced higher levels of posttraumatic stress symptoms and acute stress during the COVID-19 outbreak (118).…”
Section: Factors Related To Infection Exposurementioning
confidence: 96%
“… 18 Until now, COVID-19 infection by medical staff during work has not been commonly found in Korea, 19 but it has been shown that even with low exposure risk, healthcare workers are under emotional stress. 20 Damage to medical staff due to self-isolation after exposure is also an important factor to consider.…”
Section: Priority Setting Of Vaccinationmentioning
confidence: 99%
“…Park et al (2020) reported that healthcare providers who were in charge of COVID-19 screening or exposed to confirmed cases were more likely to be depressed than workers in rare contact departments. Depressive symptoms experienced by nurses can increase turnover intention (Pang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 outbreak, 44% of frontline nurses in emergency departments had depression (An et al 2020), which is believed to be due to the high likelihood of coming into contact with patients with suspected symptoms, such as fever. Park et al (2020) reported that healthcare providers who were in charge of COVID-19 screening or exposed to confirmed cases were more likely to be depressed than workers in rare contact departments. Depressive symptoms experienced by nurses can increase turnover intention (Pang et al 2020).…”
Section: Introductionmentioning
confidence: 99%